Informal Values and Formal Policies: A study of Japanese Technology Policy and Significance for India - Saradindu Bhaduri; Janashruti Chandra (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The main objective of this paper is to analyse some aspects of Japanese policy in the post World War-II period and understand how the various informal institutions (shared mental models) have influenced key dimensions of technology strategy with regard to the nature and trajectory of activities it sought to promote. Previous studies have mainly focused on industrial policy on the basis of the White Papers published by the Ministry of International Trade and Industry (MITI). Our study, in contrast, focuses exclusively on technology policies by examining the White Papers on Science and Technology (Kagakugijutsu Hakusho) published by the Ministry of Education, Culture, Sports, Science and Technology (MEXT). We then endeavour to understand the significance of our findings for policy making in India. However, the limited scope of this undertaking makes our results indicative in nature.
Keywords: O17; O31; Z13; 330; Informal values; institutions; culture; norm; technology; MITI; Technologiepolitik; Wirkungsanalyse; Japan; Indien